THE ROLE OF UNEVEN AGRICULTURAL BUSINESS GROWTH IN SHAPING THE SOCIO-ECONOMIC LANDSCAPE OF RURAL REGIO - Белей (Belei), Cвітлана (Svitlana); Lopatynskyi, Yurii; Лагодин, Назар; Nezhyd, Yuliia; Petrukha, Nina (AGNANIMITAS , CESKOSLOVENSKE ARMADY 300, HRADEC KRALOVE, CZECH REPUBLIC, 2024)
The role of the agricultural sector in ensuring food security and the economic development of countries during the post-pandemic period and the spread of the consequences of the Russia-Ukraine war on global markets is crucial for maintaining food security, supporting domestic demand for agricultural products and ensuring a country's economic resilience. Therefore, the asymmetric development of the agricultural business is relevant, given the need to prevent its potential adverse effects on the overall socio-economic condition of rural areas. This scientific article aims to form the conceptual-categorical framework for the asymmetric development of the agricultural business and to study the current state and prospects for developing rural areas in the EU. Literature analysis, comparative analysis, and methods of systematisation and generalisation were among the general scientific methods of cognition used to form the conceptual-categorical framework and substantiate the problem of asymmetric agricultural business development. During the research, statistical data analysis was used to define the initial data for calculating the cumulative shares of income and the area of agricultural land, forming the Lorenz curve and further calculating the Gini coefficient. Based on the calculation of the Gini Index, the overall level of asymmetry in the development of the agricultural sector of European countries was determined. The obtained value of this index, G = 0.8, which lies within the range 0 ≤ G < 0.3, indicates a high level of socio-economic equality in the rural areas of EU member states, despite the potential food crisis and disruptions to sales markets due to external damaging factors. The concept of asymmetric development of the agricultural business is characterised by the uneven distribution of critical resources for the production of agricultural products between enterprises that differ in scale or the level of development in their regions of operation. A high level of asymmetry leads to the spread of negative phenomena in the socio-economic environment of rural areas, such as depopulation, unemployment, and a decline in the quality of regional infrastructure. To prevent excessive asymmetry, EU countries are implementing systematic measures to financially support specific agricultural enterprises and improve infrastructure, particularly logistics, in rural areas, which is reflected in the low level of inequality between rural areas in different regions and EU member states.
THE ROLE OF UNEVEN AGRICULTURAL BUSINESS GROWTH IN SHAPING THE SOCIO-ECONOMIC LANDSCAPE OF RURAL REGIO
Бізнесу та управління персоналом
Keywords: Agricultural business, rural areas, uneven regional development, agriculture, production, productivity, competitiveness..